‘I can’t say that anything has changed’: parents of autistic young people (16–25 years) discuss the impact of the Children and Families Act in England and Wales - Crane, Laura; Davies, Jade; Fritz, Anne; Portman, Kerrie; O’Brien, Sarah; Worsley, Alison; Remington, Anna (Frontiers in Education, 2023)
In 2014, changes to special educational needs and disability (SEND) legislation were introduced in England and Wales. These reforms aimed for young people and their families to receive the help and support they need, have a say regarding their support needs, and achieve better outcomes. Here, we examine the views of parents of autistic young people (16-25 years) regarding the impact of the reforms, several years after their introduction. In total, 115 parents of autistic young people (16-25 years) in England and Wales took part in our research: 84 completed an online survey, one took part in an interview, and 30 participated in both the survey and interview. Quantitative data, collected via the online survey, were analyzed descriptively. Qualitative data, collected via the survey and interview, were analyzed using inductive thematic analysis. Parents overwhelmingly reported that their experiences had not improved since the introduction of the SEND reforms. This experience impacted their own, and their children's, wellbeing. Parents felt that the reforms were simply delaying the inevitable, and there was still limited support for them or their children as they transitioned to adulthood. Overall, despite promises of a radically different system, and the potential of these reforms, parents reported that little had changed for them or their children since the introduction of the Children and Families Act.